STRATEGY TO EFFECTIVELY MAKE E-KTP BY THE POPULATION AND CIVIL REGISTRATION OFFICE OF NAGEKEO DISTRICT - Frederikus Antonius Mana; Syahrabuddin H. Enala; Muhammad N. Prasetya; Rachmat AP. Parukka (Yayasan Nusantara Hasana Berdikari, 2024)
Effective and efficient public service is one of the main objectives of the government in organizing government. One form of important public service is the issuance of Population Identification Cards (E-KTP) by the Population and Civil Registration Service (Dukcapil). This study aims to analyze the implementation of the